Determinant of Transfer Pricing With Corporate Income Tax as Intervening Variables (Studies on Companies in the Field of Consumer Good Industry Listed on the Indonesia Stock Exchange Period for 2014-2020) - Intan Permatasari, Fitri; Apollo Daito (Dinasti Publisher, 2022)
Globalization drives cross-border transactions, including the transactions made by the multinational company, and creates a phenomenon of transfer pricing that becomes the attention of both local and overseas tax authorities. This phenomenon may happen due to the possibility of profit shifting by multinational companies. Thus, this research analyzes transfer pricing as the dependent variable and foreign ownership and profitability as independent variables. For the intervening variable, the researcher chose the income tax. This research uses purposive sampling with secondary data from companies listed on the Indonesian Stock Exchange in the category of Consumer Goods Industry in 2014–2020. The results show that foreign ownership, profitability, and corporate income tax simultaneously have significant effects on transfer pricing. While foreign ownership is negatively significant to transfer pricing, profitability and corporate income tax do not affect transfer pricing. Furthermore, corporate income tax cannot mediate the influence of foreign ownership and the profitability of transfer pricing.